Extending the Cutoff Wavelength of Thermophotovoltaic Devices via Band Structure Engineering - Licht, Abigail. (2018)
Abstract: Thermophotovoltaics (TPVs) convert infrared radiation, or heat, into electricity via a photovoltaic diode. While TPVs can in principle convert radiation from any heat source, in practice they have been limited to high temperature applications due to the relatively large bandgap diodes employed. Development of narrow bandgap TPV diodes is required to optimally convert longer wavelength radiation from lower temperature sources. Overcoming the intrinsic limit of these reduced bandgap diodes, however, is no trivial matter. As the bandgap of a TPV diode decreases, the intrinsic carrier concentrations and parasitic recombination increase, leading to large dark currents. The increased dark current causes the open-circuit voltage and power of the diode to drop, rendering narrow bandgap TPV diodes inoperable. Our research aims to extend the operational cut-off wavelength of TPV devices to both a) more optimally convert the incident radiation from existing heat sources and b) enable lower temperature applications. With this goal in mind, we investigate a monovalent barrier structure, in which a wide bandgap barrier is inserted into the PN diode, for TPV devices. The barrier structure has proven successful at reducing dark currents in infrared photodetectors, which operate at low temperatures and reverse biases. TPV diodes must operate at higher temperatures, where the balance of dark current mechanisms differs. Here we explore the extent to which a monovalent barrier could be effective in reducing the dark current in narrow bandgap TPVs. The barrier diode design is facilitated by the use of superlattice structures, which consist of alternating nanometer-scale layers of materials. Unlike bulk materials, where the electronic bands are fixed, the electronic bands of these structures can be tuned by varying the thickness and periodicity of the superlattice layers. In this work we use the 8x8 k·p method to design the band offsets for a barrier structure consisting of III-V superlattice materials. Structures were grown using molecular beam epitaxy and fabricated into diodes using standard photolithography methods. Dark current measurements were taken to examine the effect of a barrier structure on TPV performance.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Electrical Engineering.; Advisor: Thomas Vandervelde.; Committee: Rodolfo Salas, Matthew Panzer, and Kevin Grossklaus.; Keyword: Energy.